Synthesis of enantiopure cyclic amino acid derivatives via a sequential diastereoselective Petasis reaction/ring closing olefin metathesis process. Issue 2 (15th February 2017) - Morozova, Veronika A.; Beletskaya, Irina P.; Titanyuk, Igor D.
Graphical abstract: Abstract: A novel approach to the synthesis of enantiopure cyclic amino esters is reported. The utilization of allylboronic acid together with ( S )-α-methylbenzylamine as a chiral auxiliary in the Petasis/Mannich reaction led to the formation of allylglycine derivatives in good yield and with high diastereoselectivity. Subsequent esterification, N-allylation followed by ring-closing metathesis (RCM) reaction enabled the preparation of enantiomerically pure cyclic α-amino acid derivatives. Abstract : (2 R )- N -[( S )-1-Phenylethyl]pent-4-enoic acid: C13 H17 NO2 D.e. 86% [by 1 H NMR] [ α ]D 20  = −18.3 ( c 0.006, 1 M HCl, de 86%). Source of chirality: starting compound and asymmetric synthesis (Petasis reaction) Absolute configuration: ( R, S ) Abstract : (2 R )- N -[( S )-(1-Phenylethyl)amino]pent-4-enoic acid methyl ester: C14 H19 NO2 D.e. >99% [by 1 H NMR] [ α ]D 20  = −22.7 ( c 0.86, CHCl3 ) Source of chirality: starting compound and diastereomer separation Absolute configuration: ( R, S ) Abstract : (2 R )- N -[( S )-(1-Phenylethyl)amino]pent-4-enoic acid ethyl ester: C15 H21 NO2 D.e. >99% [by 1 H NMR] [ α ]D 20  = −76.8 ( c 0.63, CHCl3 ) Source of chirality: starting compound and diastereomer separation Absolute configuration: ( R, S ) Abstract : (2 S )- N -[( S )-(1-Phenylethyl)amino]pent-4-enoic acid ethyl ester: C15 H21 NO2 D.e. >99% [by 1 H NMR] [ α ]D 20  = −23.3 ( c 0.086, CHCl3 ) Source of chirality: starting compound and diastereomer separation Absolute configuration: ( S, S ) Abstract : Methyl ( R )-1-[( S )-1-phenylethyl]-1, 2, 3, 6-tetrahydropyridine-2-carboxylate: C15 H19 NO2 D.e. >99% [by 1 H NMR] [ α ]D 20  = +22.9 ( c 0.87, CHCl3 ). Source of chirality: starting compound and diastereomer separation Absolute configuration: ( R, S ) Abstract : Ethyl ( R )-1-[( S )-1-phenylethyl]-1, 2, 3, 6-tetrahydropyridine-2-carboxylate: C16 H21 NO2 D.e. >99% [by 1 H NMR] [ α ]D 20  = +65.8 ( c 0.456, CHCl3 ). Source of chirality: starting compound and diastereomer separation Absolute configuration: ( R, S ) Abstract : Ethyl ( S )-1-[( S )-1-phenylethyl]-1, 2, 3, 6-tetrahydropyridine-2-carboxylate: C16 H21 NO2 D.e. >99% [by 1 H NMR] [ α ]D 20  = −61.0 ( c 0.3, CHCl3 ) Source of chirality: starting compound and diastereomer separation Absolute configuration: ( S, S )